Plan de comercialización del queso elaborado artesanalmente en la ciudad de Caluma, provincia Bolívar, año 2012 - Arana Vasquez, Virginia Austreberta (2015)
The Dealers & Distributors Association of Dairy Products and its Derivatives has a legal life of approximately 9 years, during which it has had to face a competitive and dynamic market that is growing every day; generating a significant decrease in sales; why the following research project which aims to solve the above problem is proposed. With the design of the Marketing Plan as a tool to perform administrative management projects combining market 4Ps are: Product, Price, Place, Promotion and implementation of differentiation strategies that allow the Dealers & Distributors Association of Dairy Products and its Derivatives impose its new image in the market and impact a used to buy an unbranded product groups, through an attractive product presentation, accompanied by excellent quality and reasonable price that will certainly attract positioning suitable for handmade cheeses that will make the difference with its competitors